2011
DOI: 10.2174/138945011795906570
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Based Drug Delivery Systems for Cancer Treatment

Abstract: It is a fact that chemotherapy agents have little specificity for cancer cells, this leading to low concentrations into the tumor interstititum and severe side effects on healthy tissues. The formulation of lipid-based nanomedicines against cancer has been hypothesized to improve drug localization into the tumor tissue and to increase the anticancer efficacy of concentional drugs, while minimizing their systemic adverse effects. In this review, special attention is devoted to the analysis of the state-of-the-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 0 publications
0
42
0
1
Order By: Relevance
“…The profit of this kind of drug delivery systems is that the nanoparticle core can be within the nanostructure without being affected by possible external modifications via standard liposomal functionalization techniques (Arias et al, 2011a). Another example of magnetoliposomes includes those synthesized thanks to magnetotactic bacteria, and they are also called magnetosomes, having a typical size of ≈ 35 nm (Lang et al, 2007).…”
Section: Stabilization Methodsmentioning
confidence: 99%
“…The profit of this kind of drug delivery systems is that the nanoparticle core can be within the nanostructure without being affected by possible external modifications via standard liposomal functionalization techniques (Arias et al, 2011a). Another example of magnetoliposomes includes those synthesized thanks to magnetotactic bacteria, and they are also called magnetosomes, having a typical size of ≈ 35 nm (Lang et al, 2007).…”
Section: Stabilization Methodsmentioning
confidence: 99%
“…The hydrophilic and hydrophobic bilayer cores entrap hydrophilic and lipophilic drugs, respectively. Liposomes have been demonstrated to prolong the blood-circulation time of drugs, to alter the pharmacokinetics and distribution of P-gp inhibitors in vivo, and to increase the drug concentration in the tumor cells, while reducing the impact on normal tissues, thus exerting toxicity to enhance the effects of chemotherapy (15)(16)(17)(18)(19)(20)(21). A study by Zhou et al (22), which investigated MDR reversal using doxorubicin (DOX) liposomes in vitro, demonstrated that DOX liposomes were mainly detected in the nucleus of human breast cancer P-gp overexpression cells (MCF-7/Adr) with an increased toxicity, and exhibited a stronger cellular retention capacity in human carcinoma KBv200 cells.…”
Section: Liposomesmentioning
confidence: 99%
“…The first is usually referred to as "passive targeting", suggesting that the drug-loaded nanocarrier is passively retained in areas with increased microvascular permeability. 7,8 The second is known as "active targeting", which may result in an even greater gradient of drug concentration between the intact and injured tissue due to the specific interaction of the tissue-recognition ligand engrafted on the surface of the carrier and a unique disease marker expressed either on the cell membrane or inside the cell. 9 This interaction results in accumulation of the drug-enriched nanocarrier in the tissue of interest with subsequent release of the drug during biodegradation of the particle coating.…”
Section: Introductionmentioning
confidence: 99%